2020
DOI: 10.1111/cea.13686
|View full text |Cite
|
Sign up to set email alerts
|

Association between biomarkers and house dust mite sublingual immunotherapy in allergic asthma

Abstract: Background House dust mite (HDM) sublingual immunotherapy (SLIT) has demonstrated efficacy in clinical trials of patients with asthma. Airway inflammation is a characteristic of respiratory allergy, but its relationship to SLIT remains unclear. Objective We evaluate the association between clinical outcomes with pulmonary function and biomarkers in before and after HDM SLIT (UMIN Number 000022390). Methods One hundred twelve patients with asthma sensitized to HDM were randomized to add‐on 6 standardized qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…The asthma phenotypes for which AIT is effective remain to be established. Hoshino et al [ 31 ] reported that HDM-SLIT is effective in asthma with high FeNO or high serum periostin levels, suggesting that the effect of AIT may be higher in type 2-dominant asthma. Di Lorenzo et al [ 32 ] reported that the therapeutic effect of AIT is high in patients with a specific IgE/total IgE of 16.2 or higher.…”
Section: Discussionmentioning
confidence: 99%
“…The asthma phenotypes for which AIT is effective remain to be established. Hoshino et al [ 31 ] reported that HDM-SLIT is effective in asthma with high FeNO or high serum periostin levels, suggesting that the effect of AIT may be higher in type 2-dominant asthma. Di Lorenzo et al [ 32 ] reported that the therapeutic effect of AIT is high in patients with a specific IgE/total IgE of 16.2 or higher.…”
Section: Discussionmentioning
confidence: 99%
“…Other immunoglobulins such as IgA and IgG are not reported to be pre-SLIT prognostic biomarkers. Pre-SLIT serum periostin, which is induced by type 2 cytokines in inflammatory diseases, is also reported as a biomarker for predicting SLIT in allergic rhinitis or asthma [11,12]. Baseline levels of IL-10 and IL-35, both of which are produced by Treg cells, are shown to be significantly correlated with the clinical efficacy of SLIT [8].…”
Section: Biomarkers For Predicting the Efficacy Of Slitmentioning
confidence: 99%
“…Although elevated serum-specific IgE accompanied by allergic symptoms is needed to start SLIT, a clear association has not been shown between the pre-treatment-specific IgE level and clinical response. Some reports show that serum-specific IgE and the specific IgE-to-total IgE ratio before treatment can be prognostic biomarkers [8,9], but others show no evidence to support serum IgE as a prognostic biomarker [10,11]. Other immunoglobulins such as IgA and IgG are not reported to be pre-SLIT prognostic biomarkers.…”
Section: Biomarkers For Predicting the Efficacy Of Slitmentioning
confidence: 99%
“…Other work covered the issue of product availability for venom immunotherapy in the UK, 115 epidemiology of allergic and respiratory disease 116‐119 , 120 , 121 occupational allergies, 122‐124 advances in allergy diagnostics 125‐133 , 134 , 135 , 136 , animal model work 137 138 , 139 , 140 , 141 , investigation of infant airway epithelium, 142 a possible association between tree pollen exposure and reduced lung function 143 and evaluations of allergy service delivery 144‐147 …”
Section: Other Areas Of Interestmentioning
confidence: 99%